BIAS GENDER PADA KOMUNIKASI ANTAR PEKERJA PERHOTELAN: STUDI KASUS PADA HOTEL GRAND KEISHA YOGYAKARTA - Palupi Widayati (Universitas Lambung Mangkurat, 2020)
This article explains about gender bias in the hospitality sector, through the recruitment process at the Hotel Grand Keisha Yogyakarta. The method used of this research is a qualitative description with participatory observation and interviews, involving six sources, each a male manager and a female staff member from three selected departments. The three selected departments are housekeeping, food and beverages service department (FBS), and human resources development (HRD). This research uses gender culture theory, gender bias, and employee recruitment. The results obtained that gender bias can’t be seen only on one side, only from the recruitment process, but gender bias also can be phased from the start of recruitment process untill the work prosess. The process of communication and patterns of interaction that occur between workers show a state of gender bias and show the point of views about gender. The highest degree of gender bias is seen from workers with staff and supervisor positions, while manager positions have a lower degree of bias. This research can be developed with doing interviews all departments or even comparing with other hotels with different concepts.